Migrants and Religion: Paths, Issues, and Lenses A Multidisciplinary and Multi-Sited Study on the Role of Religious Belongings in Migratory and Integration Processes - Zanfrini, Laura (Brill, 2020)
Despite the worldwide dramatic spread of religious-based discriminations, persecutions, and conflicts, both official data and academic literature have underestimated their role as a root cause of contemporary migrations. This multidisciplinary study aims to overcome this gap. Through an unprecedented collection of theoretical analysis and original empirical evidence, the book provides unique data and insights on the role of religion in the trajectories of asylum seekers and migrants - from the analysis of the religious geography of sending countries to the role of spirituality as a factor of resilience and adaptation. By enhancing both academic and political debate on these issues, the book offers the possibility of regaining awareness of the close link between religious freedom and the quality of democracy. Readership: Students attending courses of Sociology, Law, Psychology, Political Science, International Relations, Theology; scholars of the above mentioned fields; religion education's teachers; people from cultural, charity, or faith-based organizations and NGOs; practitioners involved in the field of reception and integration of migrants and asylum seekers; policy-makers and public administration officers.